Impact of irrigation water quality on human norovirus surrogate survival during leafy green production - Wu, Xi; Moyne, Anne-laure; Ramos, Thais De Melo; Harris, Linda J.; DiCaprio, Erin (Frontiers in Plant Science, 2023)
The impact of water quality on the survival of human norovirus (NoV) was determined in irrigation water field run-off (tail water) and well water from a representative Central Coast vegetable production site in the Salinas Valley, California. Tail water, well water, and ultrapure water samples were inoculated separately with two surrogate viruses for human NoV—Tulane virus (TV) and murine norovirus (MNV)—to achieve a titer of 1×105 plaque forming units (PFU)/ml. Samples were stored at 11, 19, and 24℃ for 28 days. Additionally, inoculated water was applied to soil collected from a vegetables production site in the Salinas Valley or to the surface of romaine lettuce leaves, and virus infectivity was evaluated for 28 days in a growth chamber. Virus survival was similar for water stored at 11, 19, and 24℃ and there was no difference in infectivity based on water quality. After 28 days, a maximum 1.5 log reduction was observed for both TV and MNV. TV decreased by 1.97-2.26 log and MNV decreased by 1.28-1.48 logs after 28 days in soil; infectivity was not influenced by water type. Infectious TV and MNV were recovered from lettuce surfaces for up to 10 and 7 days after inoculation, respectively. Across the experiments there was no significant impact of water quality on the stability of the human NoV surrogates. Overall, the human NoV surrogates were highly stable in water with a less than 1.5 log reduction over 28 days and no difference observed based on the water quality. In soil, the titer of TV declined by approximately 2 logs over 28 days, while MNV declined by 1 log during the same time interval, suggesting surrogate-specific inactivation dynamics in the soil tested in this study. A 5-log reduction in MNV (day 10 post inoculation) and TV (day 14 post inoculation) was observed on lettuce leaves, and the inactivation kinetics were not significantly impacted by the quality of water used. These results suggest that human NoV would be highly stable in water, and the quality of the water (e.g., nutrient content, salinity, and turbidity) does not significantly impact viral infectivity.